2018
DOI: 10.1111/1440-1630.12453
|View full text |Cite
|
Sign up to set email alerts
|

Occupational therapy publications by Australian authors: A bibliometric analysis

Abstract: The volume of occupational therapy peer-reviewed literature has grown over the last two decades. Australian authors have and continue to make significant contributions to the occupational therapy body of knowledge nationally and internationally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 18 publications
0
11
0
4
Order By: Relevance
“…However, our data also show that collaboration has steadily increased, especially since 2010. A previous bibliometric study on occupational therapy publications by Australian authors reported a variation of the co-authorship rate from 1.3 in 1991 to 4.2 in 2015 [ 12 ]. This upward trend can be explained by the need for larger, more statistically powerful studies, the availability of funding to support cross-national data collection, and the availability and ease of use of social networks as a means to increase dialogue between research experts [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our data also show that collaboration has steadily increased, especially since 2010. A previous bibliometric study on occupational therapy publications by Australian authors reported a variation of the co-authorship rate from 1.3 in 1991 to 4.2 in 2015 [ 12 ]. This upward trend can be explained by the need for larger, more statistically powerful studies, the availability of funding to support cross-national data collection, and the availability and ease of use of social networks as a means to increase dialogue between research experts [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The growth of scientific production has strengthened the use of bibliometrics in occupational therapy, and the first bibliometric studies on different issues of this discipline appeared in the 1980s. Most of these studies analyzed the journals considered to be most representative of the subject area [ 9 , 10 , 11 ], while other authors studied a country or institution such as Brown et al [ 12 ] who analyzed the research publications by Australian authors. Other researchers explored the scientific literature on a specific subject area of occupational therapy, for example, Larsson, Haglund, and Hagberg [ 13 ] focused on geriatrics, Gutman and Raphael-Greenfield [ 14 ] focused on mental health, and Castro-Alzate et al [ 15 ] focused on mirror therapy.…”
Section: Introductionmentioning
confidence: 99%
“…journals that publish discipline-related research [18]) concerning occupational therapy. There are several profession-specific journals relating to occupational therapy but not all have a journal impact factor [17,18]. To include articles based only on journal impact factor, there is a risk that relevant articles concerning occupational therapy will be excluded [18] since scholars in occupational therapy do not always choose journals to publish in based on impact factor [20].…”
Section: Selection Of Journalsmentioning
confidence: 99%
“…To include articles based only on journal impact factor, there is a risk that relevant articles concerning occupational therapy will be excluded [18] since scholars in occupational therapy do not always choose journals to publish in based on impact factor [20]. Thus, in this review, journals were selected on the basis of the following criteria: peer-reviewed occupational therapy journals, published in English and accessible through the electronic databases Medline, OTDBase, and Cumulative Index to Nursing and Allied Health Literature (CHINAL) [17]. The selected journals are presented in Table 1.…”
Section: Selection Of Journalsmentioning
confidence: 99%
See 1 more Smart Citation